Exploring the Linkages Between Demingâs Principle, World-Class Company, Operational Excellence, and Company Performance in an Oil and Gas Industry Setting - Ciptono, Wakhid Slamet (Gadjah Mada International Journal of Business, 2005)
This study explores the linkages between Demingâs Principle, World-Class Company, Operational Excellence, and Company Performance in the Indonesiaâs oil and gas industry. The aim of this study is to examine the causal relationships model between the Demingâs Principle (DP), World-Class Company (WCC), Operational Excellence (OE), and Company Performance (Monetary Gain Performance or MGP and Value Gain Performance or VGP). The author used 140 strategic business units (SBUs) in 49 oil and gas companies in Indonesia. The survey was administered to every level of management at each SBU (Top, Middle, and Low Level Management). A multiple informant sampling unit is used to ensure a balanced view of the relationships between the research constructs, and to collect data from the most informed respondents on different levels of management. A total of 1,332 individual usable questionnaires were returned thus qualified for analysis, representing an effective response rate of 50.19 percent. Path analysis and structural equation modeling (SEM) are used to analyze the effect of Demingâs principle on company performance and to investigate the interrelationships between Demingâs principle, world-class company, operational excellence, and company performance. The results show that Demingâs Principle has significant positive and indirect effect on company performance (monetary gain performance and value gain performance). Although the Demingâs Principle has no significant direct effects on company performance, the Demingâs Principle has significant positive effects on the intervening variables (world-class company and operational excellence). The result also shows that a complete model fit and the acceptable parameter level that indicate the overall parameter are good fit between the hypothesized model and the observed data. By concentrating on a single industry (oil and gas), SEM specification of the causal relationship model between five constructs can be more complete and specific because unique characteristics of the oil and gas industry can be included (upstream and downstream chain activities). Finally, the particular design of the research and the findings suggest that the structural model of the study has a great potential for replication to manufacturing as well as service operations.